Effects of Plant Functional Group Loss on Soil Microbial Community and Litter Decomposition in a Steppe Vegetation - Xiao, Chunwang; Zhou, Yong; Su, Jiaqi; Yang, Fan (Frontiers in Plant Science, 2017)
Globally, many terrestrial ecosystems are experiencing a rapid loss of biodiversity. Continued improvements in our understanding of interrelationships between plant diversity and soil microbes are critical to address the concern over the consequences of the decline in biodiversity on ecosystem functioning and services. By removing forbs, or grasses, or, to an extreme scenario, both forbs and grasses in a steppe vegetation in Inner Mongolia, we studied how plant functional group (PFG) loss affects soil microbial community composition using phospholipid fatty acid analysis (PLFA) and litter decomposition using a litter-bag method. PFG loss significantly decreased above- and below-ground plant biomass, soil microbial biomass carbon (SMBC) and nitrogen (SMBN), but had no effect on the ratio of SMBC to SMBN. Although the ratio of fungal to bacterial PLFAs remained unaffected, PFG loss significantly reduced the amount of bacterial, fungal, and total PLFAs. PFG loss decreased litter monthly mass loss and decay constant, and such decrease was significant when both forbs and grasses were removed. Our results provide robust evidence that PFG loss in grassland ecosystem can lead to a rapid response of soil microbial activity which may affect litter decomposition and soil nutrient cycling, suggesting that the assessment of plant-microbe interactions in soils is an integral component of ecosystem response to biodiversity loss.